Growth Enhancement and Nitrogen Loss in ZnOxNy Low-Temperature Atomic Layer Deposition with NH3 - Kim, Soo Hyun; Pyeon, Jung Joon; Lee, Woo Chul; Jeong, Doo Seok; Baek, Seung-Hyub; Kim, Jin-Sang; Kim, Seong Keun (American Chemical Society, 2015)
The growth behavior and properties of ZnOxNy (ZnON) films grown by atomic layer deposition (ALD) with diethylzinc (DEZ), H2O, and NH3 were investigated. Although no growth of a ZnNx film occurs at 150 degrees C from DEZ and NH3, the ZnON film thickness is increasingly saturated by increasing ZnNx subcycles in a supercyde up to three successive ZnNx subcydes. The adsorbed NH3 during the injection step of NH3 induces the chemisorption of DEZ on the surface, consequently resulting in the growth enhancement. The optical band gap of the films decreases from 3.25 to 3.0 eV with increasing ZnNx subcycles. The resistivity of the films is tuned in the range from 4 x 10(-2) to 1 X 10251 cm by the variation of the ZnNx subcydes. However, the nitrogen concentration in the films is limited to approximately 2 at. % even at very high ZnNx cycles. The low nitrogen concentration is attributed to the exchange reaction of NH3 on the ZnON surface with H2O injected during the following step. These intriguing phenomena are not observed in the ALD of Al2OxNy with trimethylaluminum, which has a similar ligand structure as DEZ, H2O, and NH3. This finding demonstrates that the catalytic effect of NH3 adsorbed on the ZnO surface is critical for the growth enhancement in the ALD of ZnON.
Keywords: TIN THIN-FILMS; SURFACE-CHEMISTRY; EPITAXY GROWTH; HIGH-MOBILITY; AMMONIA; ADSORPTION; MECHANISM; SILICA; TICL4; SIO2